Theoretical Enhancement of Point Resistance in Sandy Soils Using Bio-Inspired Cranial Asperity Ratios - Candra, Agata Iwan; Munawir, As'ad; Zaika, Yulvi; Suryo, Eko Andi (Salehan Institute of Higher Education, 2026)
This study aims to enhance the bearing capacity of pile foundations in sandy soils through a bio-inspired approach by modifying Meyerhof’s empirical equation using a cranial correction factor. The adjustment considers the geometric influence of the asperity length–height ratio (L/H 20, 26.67, and 33.33) applied to different pile diameters. The analysis was carried out theoretically by calculating point resistance (Qp) using the modified equation, followed by validation through ANOVA and the nonparametric Mann–Whitney test. The results indicate that an L/H ratio of 20 provides the most significant improvement in Qp, ranging from 11.7% to 465.8% compared to the conventional Meyerhof model, particularly at lower D/B ratios where stress concentration can be optimally mobilized. Larger ratios such as 26.67 and 33.33 also improve capacity, though less effectively than L/H 20, yet still outperform unmodified foundations. The correction factors obtained, ranging from Cᵣ 1.07 to 5.66, demonstrate the substantial contribution of geometric modification to load transfer efficiency. The novelty of this research lies in integrating anisotropic interface properties into the classical Meyerhof model, thereby bridging the gap between isotropic predictions and anisotropic experimental evidence. Accordingly, the developed theoretical framework not only strengthens the basis for calculating pile bearing capacity but also opens new avenues for bio-inspired foundation design that is more efficient and sustainable.